Application of the exponential grey model on the maintenance cost prediction for a large scale hospital / Eksponentinio pilkojo modelio taikymas prognozuojant didelės ligoninės eksploatacines sąnaudas - Tzu-Ping Lo (International Journal of Strategic Property Management, 2012)
Realizing the maintenance cost distribution and predicting the future tendency are important for facility managers to efficiently arrange the limited budget. This paper collects 16,228 maintenance records of a representative hospital in Taiwan and further analyzes the cost distribution. Besides, by calculating the maintenance cost of per square meter of floor area per year (dollar/m2/year) and comparing with the previous studies, this paper also points out the relationship between maintenance cost and the operation ages. moreover, this paper establishes a hybrid grey model termed as EGM(1,1), which adopting exponential series to identify the residual error series resulted from grey model, to predict the maintenance cost. The repair cost of hospital building from 1998 to 2006 is adopted to demonstrate the applicability and practicability of EGM(1,1). Results show that the proposed model can predict the tendency precisely.